2002
DOI: 10.1021/jf020496z
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite Scavenging Activity of Sinapic Acid (3,5-Dimethoxy-4-hydroxycinnamic Acid) Isolated fromBrassica juncea

Abstract: Peroxynitrite (ONOO(-)), formed from a reaction of superoxide and nitric oxide, is one of the most potent cytotoxic species that are known to oxidize cellular constituents including essential proteins, lipids, and DNA. In this study, the ability of sinapic acid (3,5-dimethoxy-4-hydroxycinnamic acid), isolated from Brassica juncea, to scavenge ONOO(-) was investigated. The data obtained show that sinapic acid can efficiently scavenge native ONOO(-) as well as ONOO(-) derived from the peroxynitrite donor 3-morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 35 publications
3
74
0
1
Order By: Relevance
“…The oxidized DHR 123 is evaluated by the luminescence spectrometer on the excitation and emission wavelengths at 480 and 530 nm, respectively. The ONOO -scavenging activity relates to the fluorescence intensities of oxidized DHR 123 (Shin et al 2005;Zou et al 2005 is changed to a pink chromogen, which can be measured by the absorbance at 535 nm (Halliwell et al 1987;Zarena and Udaya Sankar 2009c). ORAC contains a peroxyl radical (RO 2 • ) induced by 2, 2'-azobis(2-amidinopropane) dihydrochloride and the fluorescent marker protein, i.e., fluorescein.…”
Section: Methods For Determining Antioxidant Activity Of Mangosteen Pmentioning
confidence: 99%
“…The oxidized DHR 123 is evaluated by the luminescence spectrometer on the excitation and emission wavelengths at 480 and 530 nm, respectively. The ONOO -scavenging activity relates to the fluorescence intensities of oxidized DHR 123 (Shin et al 2005;Zou et al 2005 is changed to a pink chromogen, which can be measured by the absorbance at 535 nm (Halliwell et al 1987;Zarena and Udaya Sankar 2009c). ORAC contains a peroxyl radical (RO 2 • ) induced by 2, 2'-azobis(2-amidinopropane) dihydrochloride and the fluorescent marker protein, i.e., fluorescein.…”
Section: Methods For Determining Antioxidant Activity Of Mangosteen Pmentioning
confidence: 99%
“…• -scavenging activity (Zou et al, 2002;Jalaludeen and Pari, 2011). Using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, it was found that SA had higher free radical-scavenging activity than its alkyl ester methyl sinapate or the control Trolox, a vitamin E analogue.…”
Section: Sa and Pca In Human Health And Diseasementioning
confidence: 99%
“…Anxiolytic activity, antioxidant, Cognitionimproving activity Yoon et al, 2007;Karakida et al, 2007;Zou et al, 2002. 4.…”
Section: Phenyl Isothiocyanatementioning
confidence: 99%
“…Furthermore, realization of the fact that edible mustard oil is a rich source of polyunsaturated fatty acids and phytosterols has also led to the speculation that it could also have cardio-protective effects and other health benefits. Observations made during an Seeds Anti-diabetic/ Antihyperglycemic, Antioxidant, Antiatherogenic Antifungal activity, Allergenicity, Antitumor activity Grover et al, 2002;Zou et al, 2002;Ye and Ng, 2009;Khan et al, 1996A, 1996B,1997Jyothi et al, 2007;Yadav et al, 2004;Monsalve et al, 1993. 2. Leaves Anti-oxidant, Fungicidal Activity, antiatherogenic effect.…”
Section: Pharmacology and Toxicologymentioning
confidence: 99%
See 1 more Smart Citation